Anallisis Pengembangan Produk Minuman Sinom Menggunakan Matrik SWOT dan Metode QSPM - Alwan, Mohammad Rizki I’zaz; Ismiyah, Elly; Negoro, Yanuar Pandu (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
Sinom drink product "FA DRINK" is a traditional drink that has many benefits for the body. In the development of its business, this beverage product has constraints in developing products to be accepted by the community. One of the problems encountered is the large number of similar beverage products on the market. The development strategy that will be carried out is based on strengths, weaknesses, opportunities and threats with the SWOT (Strengths, Weakness, Opportunities, and Threats) method, which is then sorted by the QSPM matrix to get a priority strategy. The results showed the total weight of the IFE matrix score of 3.319 and EFE of 2.990 so that the company was in a grow and build condition. Based on the QSPM matrix, the highest value is 6.863 and the lowest value is 5.17. Product development strategy recommendations based on the QSPM matrix are to collaborate with traders to increase sales, marketing by participating in exhibitions, improving product packaging to make it more attractive strengths